HARMONIZATION OF LAND REGULATIONS IN THE CAPITAL CITY OF THE ARCHIPELAGO (IKN) WITH NATIONAL REGULATIONS IN THE LAND SECTOR - Silalahi, Kristianto, P.H.; Tjandra, Surya (Jurnal Paradigma Hukum Pembangunan, 2025)
The construction of the National Capital in Penajam Paser, Kalimantan, has entered 25% of its construction, but it turns out that there are still several problems arising from the construction of this new capital. The infrastructure has been built, and preparations for the capital relocation have been partially implemented. The new capital city is located in Balikpapan Bay, East Kalimantan, and Nusantara. One of the problems with the construction of this national capital is the land issue because some of it is state land, and some is citizen land or customary land. As is known, Penajam Paser is located in a forestry area that also includes coastal areas and mangrove forests, residential areas, and mining. There are 21 indigenous community groups recorded as inhabiting the IKN area. As an inseparable part of the IKN development project, the existence of indigenous communities is problematic. On the one hand, these indigenous communities must be part of the region's development. Socio-historically, they have a long history in their socio-cultural life, passed down from generation to generation. On the other hand, in practice, the existence of indigenous communities was not involved in the initial formulation. The problem arises from land regulations in the IKN, whether they refer to the rules that apply nationally or if there are special rules for the IKN. If there are special rules, how can these rules be harmonized?